DINAMIKA KHULUK PERSPEKTIF FIQH DAN PUTUSAN PENGADILAN AGAMA - Jurna Petri Roszi; Hamda Sulfinadia; Eli Suryani; Elkhairati Elkhairati; Zidni ‘Ilman Nafi’an (UIN Imam Bonjol Padang, 2022)
This paper discusses the dynamics of khuluk according to fiqh and its implementation in the Religious Courts. Khuluk according to fiqh is a divorce pronounced by a husband with an agreement to pay / iwadh from his wife to her husband due to fears that the wife is unable to carry out the laws of Allah SWT. These concerns can be in the form of the wife not being able to love her husband or the inability of the wife to carry out her obligations as a wife. Meanwhile, khuluk in the Religious Courts is a divorce lawsuit filed by the wife or her legal representative because the husband violates Article 116 of the Compilation of Islamic Law as the reason for the divorce or the husband fulfills the shigat talik talak. This research is a normative-empirical legal research, namely research conducted by examining written regulations and their aspects. This research uses a legislative approach, a conceptual approach, and a comparative approach. The results of this study explain that the divorce lawsuit contained in fiqh, the Compilation of Islamic Law is different from the review of divorce claims with the Marriage Law and PP 9/1975.